Evolving cardiovascular genetic counseling needs in the era of precision medicine - Morales, Ana; Goehringer, Jessica; Sanoudou, Despina (Frontiers in Cardiovascular Medicine, 2023)
In the era of Precision Medicine the approach to disease diagnosis, treatment, and prevention is being transformed across medical specialties, including Cardiology, and increasingly involves genomics approaches. The American Heart Association endorses genetic counseling as an essential component in the successful delivery of cardiovascular genetics care. However, with the dramatic increase in the number of available cardiogenetic tests, the demand, and the test result complexity, there is a need not only for a greater number of genetic counselors but more importantly, for highly specialized cardiovascular genetic counselors. Consequently, there is a pressing need for advanced cardiovascular genetic counseling training, along with innovative online services, telemedicine, and patient-facing digital tools, as the most effective way forward. The speed of implementation of these reforms will be of essence in the translation of scientific advancements into measurable benefits for patients with heritable cardiovascular disease and their families.